Oxford Energy Forum, Issue 95 - Bassam Fattouh; David Robinson (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2014)
This issue of the Forum is dedicated to developments in Chinese energy
Keywords: 330